Prześladowania Żydów w Holandii, Francji i Belgii, 1940–1945 w ujęciu porównawczym: podobieństwa, różnice, przyczyny - Pim Griffioen; Ron Zeller (Zagłada Żydów)
At the beginning of the occupation, France, Holland and Belgium found themselves in a similar situation. But when we look at the ratio of victims and survivors during the Holocaust in Western Europe, France and Holland are polar opposites: in France 25 percent of around 320,000 Jews did not survive the persecutions, whereas the ratio in Holland was 75 percent of 140,000. Belgium lies in the middle of the scale – 40 percent dead out of 66,000 Jews. In order to understand the source of these differences, the authors compare the methods applied by the occupation authorities and their anti-Jewish policies, the involvement and the size of the local police forces and German police, as well as the jurisdictional disputes between these formations.